2020
DOI: 10.1021/acs.est.0c01676
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Biomass Sorghum GHG Reduction Potential is Similar to Maize

Abstract: Policy support for cellulosic biofuels is contingent on their achieving much greater reductions in life-cycle greenhouse gas emissions than corn starch ethanol. Biomass sorghum has been suggested as a genetically and agronomically tractable feedstock species to augment near-term cellulosic feedstock production. This study used DayCent modeling to investigate biomass sorghum production emissions relative to corn with and without stover utilization at 3,265 across the rainfed United States. Sorghum produced grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 54 publications
4
24
0
1
Order By: Relevance
“…While the maize and miscanthus cropping systems were established years prior to the study, the energy sorghum system was converted from a maize system at the onset of this study. As the energy sorghum system reaches steady state, the C and N fluxes are likely to shift drastically to reflect the perpetual reduction in biomass C and N inputs (Jin et al, 2014; Kent et al, 2020). Recent model‐based work showed the potential for energy sorghum to increase soil organic C through root biomass input in regions of the United States where rainfall, temperature and moisture availability facilitate high growth rates (Gautam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the maize and miscanthus cropping systems were established years prior to the study, the energy sorghum system was converted from a maize system at the onset of this study. As the energy sorghum system reaches steady state, the C and N fluxes are likely to shift drastically to reflect the perpetual reduction in biomass C and N inputs (Jin et al, 2014; Kent et al, 2020). Recent model‐based work showed the potential for energy sorghum to increase soil organic C through root biomass input in regions of the United States where rainfall, temperature and moisture availability facilitate high growth rates (Gautam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we predict that the N-fertilization requirements for bioenergy sorghum and nitrous oxide emissions associated with growing this crop will be lower than the values used recently to calculate bioenergy sorghum C.I. (Kent et al, 2020).…”
Section: Discussionmentioning
confidence: 70%
“…The carbon intensity (C.I.) of ethanol production from bioenergy sorghum biomass was estimated to be ~17 gCO 2 e/MJ (Kent et al, 2020), similar to corn stover, and significantly lower than corn grain ethanol (~52-105 gCO 2 e/MJ) (Scully et al, 2021;US Environmental Protection Agency, 2009). However, the estimated C.I.…”
Section: Introductionmentioning
confidence: 99%
“…Using the PRISM-ELM model, a statistical-mechanistic model based on observed soils, weather, and yield data, Lee et al (2018) found that biomass sorghum has the potential to yield >20 Mg ha -1 across a wide range in the central and eastern US. Kent et al (2020) utilized DayCent, a biogeochemical model, to find that corn tended to have a higher energy yield compared to biomass sorghum in the Midwest, but with lower annual CO2 emissions from biomass sorghum.…”
Section: Crop Modelingmentioning
confidence: 99%
“…Previous biomass sorghum modeling efforts (Lee et al, 2018;Kent et al, 2020) were performed on the scale of the continental United States, in particular for areas east of the Rocky Mountains. Therefore, using the new Agro-IBIS biomass sorghum module, a long-term simulation was run using the 0.5-degree resolution CRU-NCAR dataset ("US simulation") for comparison of average biomass yield with prior biomass sorghum modeling results (Lee et al, 2018;Kent et al, 2020) and data from yield trials (Gill et al, 2014;Lee et al, 2018). The domain of this simulation was all US regions between 75.75° W and 115.25° W longitude, which includes the Mississippi Atchafalaya River Basin, or MARB (Ferin et al, 2021).…”
Section: Model Simulationsmentioning
confidence: 99%